Difference between revisions of "Aufgaben:Problem 13"

From Ferienserie MMP2
Jump to: navigation, search
((b): upload proof later)
(this should do it)
Line 22: Line 22:
 
i.e. the characters in the sense of 2. of irreducible representations are orthonormal.
 
i.e. the characters in the sense of 2. of irreducible representations are orthonormal.
  
(b) Show that for every \( s \in {1,...,k}\) there is a nontrivial invariant subspace \( W \subset V_s\) w.r.t. \(L^{V_s}\) such that the restriction \( L_W = L^{V_s}|W \in GL(W)\) if the linear operators \(L^{V_s}\) from \(V_s\) to W defines an irreducible, unitary representation on G on the subspace W, and \(ch(L^W) = \chi_s\).
+
(b) Show that for every \( s \in {1,...,k}\) there is a nontrivial invariant subspace \( W \subset V_s\) w.r.t. \(L^{V_s}\) such that the restriction \( L_W = L^{V_s}|W \in GL(W)\) if the linear operators \(L^{V_s}\) from \(V_s\) to \(W\) defines an irreducible, unitary representation on \(G\) on the subspace \(W\), and \(ch(L^W) = \chi_s\).
  
 
(c) Conclude that the characters in the sense of 2. of irreducible representations are
 
(c) Conclude that the characters in the sense of 2. of irreducible representations are
Line 59: Line 59:
  
 
Observe that if \( [A,B] = 0\) KerA is an invariant subspace of B: let \(v\in KerA\) then  
 
Observe that if \( [A,B] = 0\) KerA is an invariant subspace of B: let \(v\in KerA\) then  
$$ABv = BAv = B0 = 0 \Rightarrow Bv \in KernA$$
+
$$ABv = BAv = B0 = 0 \Rightarrow Bv \in KerA$$
  
 
Claim 2: \((\rho_{kl},\rho_{lj})_G = \frac{1}{n}\delta_{kl}\delta_{ij}\)
 
Claim 2: \((\rho_{kl},\rho_{lj})_G = \frac{1}{n}\delta_{kl}\delta_{ij}\)
Line 90: Line 90:
 
<p style="text-align:right;">\(\square\)</p>
 
<p style="text-align:right;">\(\square\)</p>
  
now we are prepaired to prove the first part of (a): let \(\rho, \rho'\) be isomorphic \( \Rightarrow \exists \phi\) an isomorphism form V onto V' such that \(\rho(g) = \phi^{-1} \circ \rho'(g) \circ \phi \).
+
now we are prepaired to prove the first part of (a): let \(\rho, \rho'\) be isomorphic \( \Rightarrow \exists \phi\) an isomorphism form \(V\) onto \(V'\) such that \(\rho(g) = \phi^{-1} \circ \rho'(g) \circ \phi \).
  
Let T be the invertible matrix of \(\phi\) w.r.t our bases.  
+
Let \(T\) be the invertible matrix of \(\phi\) w.r.t our bases.  
  
 
$$\Rightarrow ch(\rho)(g) = tr( [\rho](g)) = tr( T^{-1} [\rho'](g) T)$$
 
$$\Rightarrow ch(\rho)(g) = tr( [\rho](g)) = tr( T^{-1} [\rho'](g) T)$$
Line 125: Line 125:
 
Claim 5: \( S^{(k,l)} = 0\)
 
Claim 5: \( S^{(k,l)} = 0\)
  
Proof: Observe that \( Ker S^{(k,l)}\) and \( Im S^{(k,l)} \) are invariant subspaces of V', V respectivly:
+
Proof: Observe that \( Ker S^{(k,l)}\) and \( Im S^{(k,l)} \) are invariant subspaces of \(V'\), \(V\) respectivly:
  
 
let \( v\in Im S^{(k,l)} \Rightarrow \exists v' \in V'\) such that \( S^{(k,l)}v' = v\)
 
let \( v\in Im S^{(k,l)} \Rightarrow \exists v' \in V'\) such that \( S^{(k,l)}v' = v\)
Line 139: Line 139:
 
(i)\(Im S^{(k,l)} = 0 \Rightarrow  S^{(k,l)} = 0 \Rightarrow \) the claim is proven
 
(i)\(Im S^{(k,l)} = 0 \Rightarrow  S^{(k,l)} = 0 \Rightarrow \) the claim is proven
  
(ii) \(Im S^{(k,l)} = V \Rightarrow S^{(k,l)} \) is surjective, because \(S^{(k,l)}\) is a linear transfrom from V' to V
+
(ii) \(Im S^{(k,l)} = V \Rightarrow S^{(k,l)} \) is surjective, because \(S^{(k,l)}\) is a linear transfrom from \(V'\) to \(V\)
  
 
Since  \(\rho'\) is irreducible eighter  
 
Since  \(\rho'\) is irreducible eighter  
  
(iii)\(Ker S^{(k,l)} = V'\) but since again \(S^{(k,l)}\) is a linear transfrom from V' to V\(\Rightarrow  S^{(k,l)} = 0 \)
+
(iii)\(Ker S^{(k,l)} = V'\) but since again \(S^{(k,l)}\) is a linear transfrom from \(V'\) to \(V\) \(\Rightarrow  S^{(k,l)} = 0 \)
  
 
(iv)\(Ker S^{(k,l)} = 0 \Rightarrow S^{(k,l)}\) is injective, with (ii) \(\Rightarrow S^{(k,l)}\) is an isomorphism \(\Rightarrow S^{(k,l)} = 0\) because of Claim 4 and because \(\rho\) and \(\rho'\) are not isomorphic.
 
(iv)\(Ker S^{(k,l)} = 0 \Rightarrow S^{(k,l)}\) is injective, with (ii) \(\Rightarrow S^{(k,l)}\) is an isomorphism \(\Rightarrow S^{(k,l)} = 0\) because of Claim 4 and because \(\rho\) and \(\rho'\) are not isomorphic.
Line 171: Line 171:
 
Proof: We know that \( \Pi_s 1\leq s\leq k\) are a family of orthogonal projections on V and range \( \Pi_s = V_s\).
 
Proof: We know that \( \Pi_s 1\leq s\leq k\) are a family of orthogonal projections on V and range \( \Pi_s = V_s\).
  
\( \Rightarrow V_s\) are orthogonal subspaces of V. Observe that \( \chi_s = \chi_{se} \in V_s\) for every s.
+
\( \Rightarrow V_s\) are orthogonal subspaces of \(V\). Observe that \( \chi_s = \chi_{se} \in V_s\) for every \(s\).
  
 
Now consider a class function \(\psi \in V_s\):
 
Now consider a class function \(\psi \in V_s\):
Line 184: Line 184:
 
<p style="text-align:right;">\(\square\)</p>
 
<p style="text-align:right;">\(\square\)</p>
  
Claim 8: \( ch(L^{V_s})(x) = \sqrt{|G|} v_{s1} \chi_s(x)\)
+
Claim 8: \((\chi_{sy}, \chi_{sx})_G = \frac{1}{v_{s1}\sqrt{|G|}} \chi_{sy}(x)\)
  
The character is a class function \( \Rightarrow ch(L^{V_s})(x) =\lambda \chi_s(x)\). Consider:
+
Proof:
 +
 
 +
$$(\chi_{sy}, \chi_{sx})_G = \frac{1}{|G|} \sum_{z\in G} \chi_{sy}(z) \chi_s(zx^{-1})^*$$
 +
 
 +
$$= \frac{1}{v_{s1}\sqrt{|G|}} \frac{1}{|G|} \sum_{z\in G} v_{s1}\sqrt{|G|} \chi_s(zx^{-1})^* \chi_{sy}(z) = \frac{1}{v_{s1}\sqrt{|G|}} \frac{1}{|G|} \sum_{z\in G} \Pi_s(z,x)^* \chi_{sy}(z)$$
 +
 
 +
Fourier Script last page: \(\Pi_s(z,x)^* = \Pi_s(x,z)\)
 +
 
 +
$$= \frac{1}{v_{s1}\sqrt{|G|}} \frac{1}{|G|} \sum_{z\in G} \Pi_s(x,z) \chi_{sy}(z) = \frac{1}{v_{s1}\sqrt{|G|}} (\Pi_s \chi_{sy} )(x) = \frac{1}{v_{s1}\sqrt{|G|}} \chi_{sy}(x)$$
 +
 
 +
<p style="text-align:right;">\(\square\)</p>
 +
 
 +
Claim 9: \( ch(L^{V_s}) \in V_s\)
 +
 
 +
Proof: Choose an orthomnormal basis \(e_1,\dots e_n\) of \(V_s\ w.r.t\ (\ ,\ )_G\Rightarrow e_i = \sum_{y\in G} \lambda_{iy} \chi_{sy}\)
 +
 
 +
\begin{align}
 +
ch(L^{V_s})(g) &= tr(L^{V_s}(g)) \\
 +
&= \sum_{j= 1}^n (e_j, L^{V_s}(g) e_j)_G = \sum_{j= 1}^n (\sum_{z\in G} \lambda_{iz} \chi_{sz}, L^{V_s}(g) \sum_{y\in G} \lambda_{iy} \chi_{sy} )_G =  \sum_{j= 1}^n \sum_{z\in G}  \sum_{y\in G} \lambda_{iz} \lambda_{iy}^* (\chi_{sz}, L^{V_s}(g) \chi_{sy} )_G \\
 +
&= \sum_{j= 1}^n \sum_{z\in G}  \sum_{y\in G} \lambda_{iz} \lambda_{iy}^* (\chi_{sz}, \chi_{sgy} )_G =  \sum_{j= 1}^n \sum_{z\in G}  \sum_{y\in G} \lambda_{iz} \lambda_{iy}^* \chi_{sz}(gy) = \sum_{j= 1}^n \sum_{z\in G}  \sum_{y\in G} \lambda_{iz} \lambda_{iy}^* \chi_{szy^{-1}}(g) \\
 +
\end{align}
 +
 
 +
<p style="text-align:right;">\(\square\)</p>
 +
 
 +
Claim 10: \( ch(L^{V_s})(x) = \sqrt{|G|} v_{s1} \chi_s(x)\)
 +
 
 +
The character is a class function and with Claim 9 \( \Rightarrow ch(L^{V_s})(x) =\lambda \chi_s(x)\). Consider:
  
 
$$ch(L^{V_s})(e) = dim V_s = tr \Pi_s $$
 
$$ch(L^{V_s})(e) = dim V_s = tr \Pi_s $$
Line 197: Line 223:
 
<p style="text-align:right;">\(\square\)</p>
 
<p style="text-align:right;">\(\square\)</p>
  
Claim 9: \( ||ch(L^{V_s})||_2^2 = dim V_s\)  
+
Claim 11: \( ||ch(L^{V_s})||_2^2 = dim V_s\)  
  
 
$$||ch(L^{V_s})||_2^2 = \frac{1}{|G|} \sum_{x\in G} |ch(L^{V_s})(x)|^2 = \frac{1}{|G|} \sum_{x\in G} |\sqrt{|G|} v_{s1} \chi_s(x)|^2 = {|G|} v_{s1}^2 \frac{1}{|G|} \sum_{x\in G} \chi_s(x)^*\chi_s(x)$$
 
$$||ch(L^{V_s})||_2^2 = \frac{1}{|G|} \sum_{x\in G} |ch(L^{V_s})(x)|^2 = \frac{1}{|G|} \sum_{x\in G} |\sqrt{|G|} v_{s1} \chi_s(x)|^2 = {|G|} v_{s1}^2 \frac{1}{|G|} \sum_{x\in G} \chi_s(x)^*\chi_s(x)$$
Line 207: Line 233:
 
$$||ch(L^{V_s})||_2 = \sqrt{dim V_s}$$
 
$$||ch(L^{V_s})||_2 = \sqrt{dim V_s}$$
  
If \( dim V_s = 1 \Rightarrow  ch(L^{V_s})(x) = \chi_s(x)\) and from Claim 3 we know that \(V_s\) is irreducible in this case W = V and we are done.
+
If \( dim V_s = 1 \Rightarrow  ch(L^{V_s})(x) = \chi_s(x)\) and from Claim 3 we know that \(V_s\) is irreducible in this case \(W = V\) and we are done.
  
 
If \( dim V_s > 1 \) we know that \(V_s\) is not irreducible, and there are at least two irreducible subspaces of \(W, W', ...\)
 
If \( dim V_s > 1 \) we know that \(V_s\) is not irreducible, and there are at least two irreducible subspaces of \(W, W', ...\)
  
W as a subspace of \(V_s\) is still orthogonal to all the other subspaces \(V_r,\ r\in \{1,...,k\}, r\neq s\) so by the same argument as before \(ch(L^W)(x) = \lambda \chi_s(x)\). Because W is irreducible:
+
\(W\) is a subspace of \(V_s\), by the same argument as before \(ch(L^W)(x) = \lambda \chi_s(x)\). Because W is irreducible:
  
 
$$||ch(L^{V_s})||_2^2 = ... = |\lambda|^2 \overset{!}{=} 1 \Rightarrow |\lambda| = 1 $$
 
$$||ch(L^{V_s})||_2^2 = ... = |\lambda|^2 \overset{!}{=} 1 \Rightarrow |\lambda| = 1 $$
Line 234: Line 260:
 
$$ (ch(L^{W_s}), ch(\rho))_G = \sum_{j=1} a_j (\chi_s, \chi_j)_G = a_s = \begin{cases} 1, & \text{if \(\rho\) and \(L^{W_s}\) are isomorphic} \\  0, & \text{if \(\rho\) and \(L^{W_s}\) are not isomorphic,} \end{cases}$$
 
$$ (ch(L^{W_s}), ch(\rho))_G = \sum_{j=1} a_j (\chi_s, \chi_j)_G = a_s = \begin{cases} 1, & \text{if \(\rho\) and \(L^{W_s}\) are isomorphic} \\  0, & \text{if \(\rho\) and \(L^{W_s}\) are not isomorphic,} \end{cases}$$
  
since \(a_s\) can't be zero for all the \(s\in \{1,...,k\}\) and can't be zero for more then one \(s\) because that would implie that \(L^{W_s}, L^{W_r}\) are isomporhic, it follows that for one particular s:
+
since \(a_s\) can't be zero for all the \(s\in \{1,...,k\}\) and can't be zero for more then one \(s\) because that would implie that \(L^{W_s}, L^{W_r}\) are isomporhic, it follows that for one particular \(s\):
  
 
$$ ch(\rho) = \chi_s$$
 
$$ ch(\rho) = \chi_s$$
Line 240: Line 266:
 
<p style="text-align:right;">\(\square\)</p>
 
<p style="text-align:right;">\(\square\)</p>
  
Note: this means that every irreducible representation of G is isomorphic to an irreducible representation that is found in the regular representation L.
+
Note: this means that every irreducible representation of \(G\) is isomorphic to an irreducible representation that is found in the regular representation \(L\).

Revision as of 11:11, 27 June 2015

Task

Let G be a finite group. In the lectures we encountered two types of functions on G which were both called characters:

1. Let \( C_1 = {e}, C_2,...,C_k\) be the conjugacy classes, and let \(v_1,..., v_k\) be the normalized eigenvectors of the Burnside matrices of G, then for all \(s \in {1,...,k}\) we defined the maps

$$ \chi : G\ \rightarrow \ \mathbb{C}$$ $$ g \mapsto \sqrt{|G|}\sum_{j=1}^k \frac{v_{sj}}{\sqrt{|C_j|}}\delta_{C_j}(g).$$

2. For any represntation \(\rho\) we defines the map \(ch(\rho):x\rightarrow Tr(\rho(x))\).

We want to show that the characters in the sense of 2. of irreducible representations are exacly the characters in the sense of 1. For all \(s \in {1,...,k}\) let

$$ V_s := Span\{x\mapsto \chi_s(xy^{-1})| y\in G\}$$

Recall that \(V_s\) is an invariant subspace of all linear transformations \(L(g), g\in G\)

(a) Let \(\rho\) and \(\rho'\) be unitary irreducible representations of G on finite dimensional complex inner product space \(V\) and \(V'\) respectivly. Show that

$$(Tr(\rho), Tr(\rho'))_G = \begin{cases} 1, & \text{if \(\rho\) and \(\rho'\) are isomorphic} \\ 0, & \text{if \(\rho\) and \(\rho'\) are not isomorphic,} \end{cases}$$

i.e. the characters in the sense of 2. of irreducible representations are orthonormal.

(b) Show that for every \( s \in {1,...,k}\) there is a nontrivial invariant subspace \( W \subset V_s\) w.r.t. \(L^{V_s}\) such that the restriction \( L_W = L^{V_s}|W \in GL(W)\) if the linear operators \(L^{V_s}\) from \(V_s\) to \(W\) defines an irreducible, unitary representation on \(G\) on the subspace \(W\), and \(ch(L^W) = \chi_s\).

(c) Conclude that the characters in the sense of 2. of irreducible representations are exactly the characters in the sense of 1.

Solution

(a)

Choose an orthonormal basis of \(V, V'\) with dimension \(n, m\) respectively. Let

$$[\rho](g) := \Big(\rho_{ij}(g)\Big)_{1\leq i,j \leq n}$$ $$[\rho'](g) := \Big(\rho'_{ij}(g)\Big)_{1\leq i,j \leq m}$$

be the matrices of \(\rho\) and \(\rho'\) relative to these bases. Set

$$ T^{(k,l)} := \Big(T^{(k,l)}{}_{i,j} \Big) = \Big(\frac{1}{|G|} \sum_{g\in G}\rho_{ki}(g)^*\rho_{lj}(g)\Big) = \Big((\rho_{ki},\rho_{lj})_G\Big)\ \text{ for} \ 1\leq k,l\leq n$$

Claim 1 : \([T^{(k,l)}, [\rho](g)] = 0\)

Proof:

$$ \big(T^{(k,l)} [\rho](g)\big)_{ij} = \sum_{a=1}^n T^{(k,l)}{}_{ia} \rho_{aj}(g) = \sum_{a=1}^n \frac{1}{|G|} \sum_{h\in G}\rho_{ki}(h)^*\rho_{la}(h) \rho_{aj}(g)$$

$$ \frac{1}{|G|} \sum_{h\in G}\rho_{ki}(h)^* \sum_{a=1}^n \rho_{la}(h) \rho_{aj}(g) = \frac{1}{|G|} \sum_{h\in G}\rho_{ki}(h)^* \rho_{lj}(hg) $$

\( z = hg \rightarrow h = zg^{-1}\)

$$ = \frac{1}{|G|} \sum_{z\in G}\rho_{ki}(zg^{-1})^* \rho_{lj}(z) = \frac{1}{|G|} \sum_{z\in G} \sum_{a=1}^n \rho_{ka}(z)^* \rho_{ai}(g^{-1})^* \rho_{lj}(z) $$

$$ = \sum_{a=1}^n T^{(k,l)}{}_{aj} \rho_{ai}(g^{-1})^* $$

since \([\rho](g)\) is a unitary matrix: \( \rho_{ai}(g^{-1})^* = \rho_{ia}(g^{-1})^{T^*} = \rho_{ia}(g^{-1})^{-1} = \rho_{ia}(g)\)

$$ = \sum_{a=1}^n T^{(k,l)}{}_{aj} \rho_{ia}(g) = \big(T^{(k,l)}[\rho](g)\big)_{ij}$$

\(\square\)

Observe that if \( [A,B] = 0\) KerA is an invariant subspace of B: let \(v\in KerA\) then $$ABv = BAv = B0 = 0 \Rightarrow Bv \in KerA$$

Claim 2: \((\rho_{kl},\rho_{lj})_G = \frac{1}{n}\delta_{kl}\delta_{ij}\)

Proof: Let \(\lambda\) be an eigenvalue of \(T^{(k,l)}\) $$ [T^{(k,l)} -\lambda \mathbb{I}, [\rho](g)] = 0$$ since the identity commutes with everything.

$$ \Rightarrow Ker(T^{(k,l)} -\lambda \mathbb{I}) \neq \{0\}$$

is an invariant subspace of \(\rho\) and because \(\rho\) is irreducible is equal to \(V\)

$$\Rightarrow T^{(k,l)} = \lambda \mathbb{I}$$

$$ \lambda n = tr T^{(k,l)} = \sum_{j=1}^n \frac{1}{|G|}\sum_{g\in G} \rho_{kj}(g)^*\rho_{lj}(g) = \sum_{j=1}^n \frac{1}{|G|}\sum_{g\in G} \rho_{jk}(g^{-1})\rho_{lj}(g) = \frac{1}{|G|}\sum_{g\in G} \rho_{lk}(e) =\delta_{lk}$$

because \( \rho(e) = e = \mathbb{I}\). For \( k\neq l \Rightarrow \lambda = 0 \Rightarrow T^{(k,l)} = 0\) and for \( k = k \Rightarrow \lambda = \frac{1}{n} \Rightarrow T^{(k,k)} = \frac{1}{n} \mathbb{I} \)

$$\Rightarrow \Big(T^{(k,l)}{}_{ij} \Big) = \frac{1}{n} \delta_{lk} \delta_{ij}$$

\(\square\)

Claim 3: \( ||ch(\rho)||_2 = 1\)

Proof:

$$ ||ch(\rho)||_2^2 = \frac{1}{|G|}\sum_{g\in G} |ch(\rho)|^2 = \frac{1}{|G|}\sum_{g\in G} tr[\rho](g)^*tr[\rho](g) = \frac{1}{|G|}\sum_{g\in G} \sum_{i=1}^n \rho_{ii}(g)^* \sum_{j=1}^n \rho_{jj}(g)$$

$$ = \sum_{i,j=1}^n (\rho_{ii}, \rho_{jj})_G = \sum_{i,j=1}^n \frac{1}{n} \delta_{ij} = 1$$

\(\square\)

now we are prepaired to prove the first part of (a): let \(\rho, \rho'\) be isomorphic \( \Rightarrow \exists \phi\) an isomorphism form \(V\) onto \(V'\) such that \(\rho(g) = \phi^{-1} \circ \rho'(g) \circ \phi \).

Let \(T\) be the invertible matrix of \(\phi\) w.r.t our bases.

$$\Rightarrow ch(\rho)(g) = tr( [\rho](g)) = tr( T^{-1} [\rho'](g) T)$$

using \( tr(AB) = tr(BA) \)

$$ = tr( [\rho'](g) T T^{-1}) = tr( [\rho'](g)) = ch(\rho')(g)$$

$$ \Rightarrow (ch(\rho), ch(\rho'))_G = (ch(\rho), ch(\rho))_G = ||ch(\rho)||_2^2 = 1$$

Now for the second part: from now on let \(\rho, \rho'\) be not isomorphic. Set

$$ S^{(k,l)} := \Big(S^{(k,l)}{}_{ij} \Big) = \Big(\frac{1}{|G|} \sum_{g\in G}\rho_{ki}(g)^*\rho'_{lj}(g)\Big) \text{ } 1\leq k\leq n,\ 1\leq l\leq m$$

which is the matrix of a linear transform from \(V'\) to \(V\).

Claim 4: \( S^{(k,l)}[\rho'](g)= [\rho](g)S^{(k,l)}\)

Proof:

$$\big(S^{(k,l)}[\rho'](g)\big)_{ij} = \sum_{a=1}^m S^{(k,l)}{}_{ia} \rho'_{aj}(g) = \sum_{a=1}^n \frac{1}{|G|} \sum_{h\in G}\rho_{ki}(h)^*\rho'_{la}(h) \rho'_{aj}(g)$$

$$ = \frac{1}{|G|} \sum_{h\in G}\rho_{ki}(h)^* \rho'_{lj}(hg) $$

\( z = hg \rightarrow h = zg^{-1}\)

$$ = \frac{1}{|G|} \sum_{z\in G}\rho_{ki}(zg^{-1})^* \rho'_{lj}(z) = \frac{1}{|G|} \sum_{z\in G} \sum_{a=1}^m \rho_{ka}(z)^* \rho_{ai}(g^{-1})^* \rho'_{lj}(z) $$

$$ = \sum_{a=1}^m \rho_{ai}(g) S^{(k,l)}{}_{aj} = \big([\rho](g)S^{(k,l)}\big)_{ij} $$

\(\square\)

Claim 5: \( S^{(k,l)} = 0\)

Proof: Observe that \( Ker S^{(k,l)}\) and \( Im S^{(k,l)} \) are invariant subspaces of \(V'\), \(V\) respectivly:

let \( v\in Im S^{(k,l)} \Rightarrow \exists v' \in V'\) such that \( S^{(k,l)}v' = v\)

$$ \rho(g)v = \rho(g) S^{(k,l)}v' = S^{(k,l)}\rho'(g)v' = S^{(k,l)} w' \Rightarrow \rho(g)v \in Im S^{(k,l)}$$

let \( v'\in Ker S^{(k,l)}\)

$$ S^{(k,l)}\rho'(g)v' = \rho(g)S^{(k,l)}v' = \rho(g)0 = 0 \Rightarrow \rho'(g)v' \in Ker S^{(k,l)}$$

Since \(\rho\) is irreducible eighter

(i)\(Im S^{(k,l)} = 0 \Rightarrow S^{(k,l)} = 0 \Rightarrow \) the claim is proven

(ii) \(Im S^{(k,l)} = V \Rightarrow S^{(k,l)} \) is surjective, because \(S^{(k,l)}\) is a linear transfrom from \(V'\) to \(V\)

Since \(\rho'\) is irreducible eighter

(iii)\(Ker S^{(k,l)} = V'\) but since again \(S^{(k,l)}\) is a linear transfrom from \(V'\) to \(V\) \(\Rightarrow S^{(k,l)} = 0 \)

(iv)\(Ker S^{(k,l)} = 0 \Rightarrow S^{(k,l)}\) is injective, with (ii) \(\Rightarrow S^{(k,l)}\) is an isomorphism \(\Rightarrow S^{(k,l)} = 0\) because of Claim 4 and because \(\rho\) and \(\rho'\) are not isomorphic.

\(\square\)


$$ \Rightarrow \big(S^{(k,l)}\big)_{ij} = \frac{1}{|G|} \sum_{g\in G}\rho_{ki}(g)^*\rho'_{lj}(g) = \big( \rho_{ki}, \rho'_{lj} \big)_G = 0$$

Now we can easly prove the second part of (a):

$$(ch(\rho), ch(\rho'))_G = \frac{1}{|G|} \sum_{g\in G} \sum_{i = 1}^n \rho_{ii}(g)^* \sum_{j = 1}^m \rho'_{ii}(g) = \sum_{i = 1}^n \sum_{j = 1}^m (\rho_{ii}, \rho'_{jj})_G = 0$$

(b)

We can use Claim 3 to determine wether \(L^{V_s}\) is irreducible, in order to do this we have to determine the character.

Claim 6: \( \chi_s\) \(s \in {1,...,k}\) is an othonormal basis of the class funcitons on G.

Proof: We know that \( \frac{\sqrt{|G|}}{\sqrt{|C_j|}} \delta_{C_j}(g)\) \(j \in {1,...,k}\) is an orthonormal basis of the class functions. And \( v_{s} \) \(s \in {1,...,k}\) are orhonormal w.r.t the standard complex inner product.

$$ ( \chi_s, \chi_t )_G = \Big( \sqrt{|G|}\sum_{j=1}^k \frac{v_{sj}}{\sqrt{|C_j|}}\delta_{C_j}(g), \sqrt{|G|}\sum_{j=1}^k \frac{v_{tj}}{\sqrt{|C_j|}}\delta_{C_j}(g) \Big)_G$$

$$ \sum_{i,j=1}^k v_{si}^* v_{tj} \Big( \frac{\sqrt{|G|}}{\sqrt{|C_i|}}\delta_{C_i}(g), \frac{\sqrt{|G|}}{\sqrt{|C_j|}}\delta_{C_j}(g) \Big)_G = \sum_{i,j=1}^k v_{si}^* v_{tj} \delta_{ij} = \sum_{j=1}^k v_{sj}^* v_{tj} = \delta_{st}$$

\(\square\)

Claim 7: Every classfunction \(\in V_s\) is a multiple of \( \chi_s\)

Proof: We know that \( \Pi_s 1\leq s\leq k\) are a family of orthogonal projections on V and range \( \Pi_s = V_s\).

\( \Rightarrow V_s\) are orthogonal subspaces of \(V\). Observe that \( \chi_s = \chi_{se} \in V_s\) for every \(s\).

Now consider a class function \(\psi \in V_s\):

$$ \psi = \sum_{j = 1}^k a_j \chi_j, \quad a_j \in \mathbb{C} $$

\(\forall r \in \{ 1,...,k \}, r\neq s\):

$$ (\psi, \chi_r)_G = \sum_{j = 1}^k a_j (\chi_j, \chi_r)_G = a_r = 0$$ $$ \Rightarrow \psi = a_s \chi_s$$

\(\square\)

Claim 8: \((\chi_{sy}, \chi_{sx})_G = \frac{1}{v_{s1}\sqrt{|G|}} \chi_{sy}(x)\)

Proof:

$$(\chi_{sy}, \chi_{sx})_G = \frac{1}{|G|} \sum_{z\in G} \chi_{sy}(z) \chi_s(zx^{-1})^*$$

$$= \frac{1}{v_{s1}\sqrt{|G|}} \frac{1}{|G|} \sum_{z\in G} v_{s1}\sqrt{|G|} \chi_s(zx^{-1})^* \chi_{sy}(z) = \frac{1}{v_{s1}\sqrt{|G|}} \frac{1}{|G|} \sum_{z\in G} \Pi_s(z,x)^* \chi_{sy}(z)$$

Fourier Script last page: \(\Pi_s(z,x)^* = \Pi_s(x,z)\)

$$= \frac{1}{v_{s1}\sqrt{|G|}} \frac{1}{|G|} \sum_{z\in G} \Pi_s(x,z) \chi_{sy}(z) = \frac{1}{v_{s1}\sqrt{|G|}} (\Pi_s \chi_{sy} )(x) = \frac{1}{v_{s1}\sqrt{|G|}} \chi_{sy}(x)$$

\(\square\)

Claim 9: \( ch(L^{V_s}) \in V_s\)

Proof: Choose an orthomnormal basis \(e_1,\dots e_n\) of \(V_s\ w.r.t\ (\ ,\ )_G\Rightarrow e_i = \sum_{y\in G} \lambda_{iy} \chi_{sy}\)

\begin{align} ch(L^{V_s})(g) &= tr(L^{V_s}(g)) \\ &= \sum_{j= 1}^n (e_j, L^{V_s}(g) e_j)_G = \sum_{j= 1}^n (\sum_{z\in G} \lambda_{iz} \chi_{sz}, L^{V_s}(g) \sum_{y\in G} \lambda_{iy} \chi_{sy} )_G = \sum_{j= 1}^n \sum_{z\in G} \sum_{y\in G} \lambda_{iz} \lambda_{iy}^* (\chi_{sz}, L^{V_s}(g) \chi_{sy} )_G \\ &= \sum_{j= 1}^n \sum_{z\in G} \sum_{y\in G} \lambda_{iz} \lambda_{iy}^* (\chi_{sz}, \chi_{sgy} )_G = \sum_{j= 1}^n \sum_{z\in G} \sum_{y\in G} \lambda_{iz} \lambda_{iy}^* \chi_{sz}(gy) = \sum_{j= 1}^n \sum_{z\in G} \sum_{y\in G} \lambda_{iz} \lambda_{iy}^* \chi_{szy^{-1}}(g) \\ \end{align}

\(\square\)

Claim 10: \( ch(L^{V_s})(x) = \sqrt{|G|} v_{s1} \chi_s(x)\)

The character is a class function and with Claim 9 \( \Rightarrow ch(L^{V_s})(x) =\lambda \chi_s(x)\). Consider:

$$ch(L^{V_s})(e) = dim V_s = tr \Pi_s $$

because the trace of a projection is the dimension of it's target space.

$$ = \frac{1}{|G|} \sum_{x\in G} \Pi_s(x,x) = \frac{1}{|G|} \sum_{x\in G} \sqrt{|G|} v_{s1}\chi_s(xx^{-1}) = \frac{1}{\sqrt{|G|}} v_{s1} \sum_{x\in G} \chi_s(e) = \sqrt{|G|} v_{s1} \chi_s(e)$$

$$ \Rightarrow ch(L^{V_s})(x) = \sqrt{|G|} v_{s1} \chi_s(x)$$

\(\square\)

Claim 11: \( ||ch(L^{V_s})||_2^2 = dim V_s\)

$$||ch(L^{V_s})||_2^2 = \frac{1}{|G|} \sum_{x\in G} |ch(L^{V_s})(x)|^2 = \frac{1}{|G|} \sum_{x\in G} |\sqrt{|G|} v_{s1} \chi_s(x)|^2 = {|G|} v_{s1}^2 \frac{1}{|G|} \sum_{x\in G} \chi_s(x)^*\chi_s(x)$$

$$ = {|G|} v_{s1}^2 (\chi_s,\chi_s)_G = {|G|} v_{s1}^2 = dim V_s$$

Now we get to the actual proof:

$$||ch(L^{V_s})||_2 = \sqrt{dim V_s}$$

If \( dim V_s = 1 \Rightarrow ch(L^{V_s})(x) = \chi_s(x)\) and from Claim 3 we know that \(V_s\) is irreducible in this case \(W = V\) and we are done.

If \( dim V_s > 1 \) we know that \(V_s\) is not irreducible, and there are at least two irreducible subspaces of \(W, W', ...\)

\(W\) is a subspace of \(V_s\), by the same argument as before \(ch(L^W)(x) = \lambda \chi_s(x)\). Because W is irreducible:

$$||ch(L^{V_s})||_2^2 = ... = |\lambda|^2 \overset{!}{=} 1 \Rightarrow |\lambda| = 1 $$

also

$$ch(L^{V_s})(e) = ... = \lambda \sqrt{|G|} v_{s1} \overset{!}{=} dim W$$

since \(\sqrt{|G|} v_{s1} > 0\) (Fourier Script page 5) and \(dim W\) is a positive integer \( \Rightarrow \lambda = 1\)

which concludes the proof.

(c)

From part (a) follows that \(L^{W_s}, L^{W_r}\) are non isomorphic for \(r\neq s\): $$ (ch(L^{W_s}), ch(L^{W_r}))_G = (\chi_s, \chi_r)_G = \delta_{rs}$$

\(ch(\rho)\) is a classfunction

$$\Rightarrow ch(\rho) = \sum_{j=1}^k a_j \chi_j$$

$$ (ch(L^{W_s}), ch(\rho))_G = \sum_{j=1} a_j (\chi_s, \chi_j)_G = a_s = \begin{cases} 1, & \text{if \(\rho\) and \(L^{W_s}\) are isomorphic} \\ 0, & \text{if \(\rho\) and \(L^{W_s}\) are not isomorphic,} \end{cases}$$

since \(a_s\) can't be zero for all the \(s\in \{1,...,k\}\) and can't be zero for more then one \(s\) because that would implie that \(L^{W_s}, L^{W_r}\) are isomporhic, it follows that for one particular \(s\):

$$ ch(\rho) = \chi_s$$

\(\square\)

Note: this means that every irreducible representation of \(G\) is isomorphic to an irreducible representation that is found in the regular representation \(L\).